Geothermobaric criteria for oil-and-gas bearing in the Dnieper-Donets Graben - Kurovets, I.M.; Hrytsyk, I.I.; Prykhodko, O.A.; Kucher, Z.I.; Kurovets, S.S. (Geofizicheskiy Zhurnal, 2025)
To evaluate exploration areas and forecast individual productive horizons of exploration for oil and gas, it is necessary to establish patterns in the location of the already explored hydrocarbon deposits. The analysis has to consider the structural and tectonic build, lithological and stratigraphic features, and hydrogeological and geothermobaric conditions of the oil and gas region. The relationship of geothermobaric parameters with the phase state of hydrocarbons in a vertical section should serve as an important factor for solving the problem. Within the Eastern oil and gas region of Ukraine, gas, oil, and gas condensate deposits are zoned. Vertical zoning of the location of hydrocarbon deposits of oil and gas horizons follows the geothermobaric criteria for the Monastyryshchensko-Sofiyivskyi and Talalaivsko-Rybalskyi oil-and-gas bearing, Hlynsko-Solokhivskyi gas-and-oil bearing and Mashivsko-Shebelinskyi gas-bearing, Rudenkivsko-Proletarskyi oil-and-gas bearing deposits of the Eastern oil and gas region of Ukraine.